KEDUDUKAN HUKUM PARA PIHAK DALAM PERJANJIAN WARALABA DI INDONESIA - Trisnadewi, Ida Ayu; Mahartayasa, Made (Kertha Semaya : Journal Ilmu Hukum, 2014)
Franchise has emerged as widely favored business concept in society currently. Conducting business under franchise concept is favored due to its profitability and many features of advantages offered by franchisor towards the franchisee. Methods conducted in composing this writing shall be normative legal research combined with statutory approach. The author shall analyze relevant regulations in respect with Status of Parties in Franchise Agreement in Indonesia. Aims of the writing shall serve to comprehend the legal status of parties in Indonesian franchise agreement. Legal standing of parties within franchise agreement shall serve on its own according to Indonesian Law.
Keywords: Franchise, legal position, franchisee, franchisor